Selected letters of Matthew Arnold - Arnold, Matthew 1822-1888 (Univ. of Michigan Press, 1993)
Selected Letters of Matthew Arnold is a collection of 216 letters by the Victorian poet and critic Matthew Arnold (1822-88). The letters are arranged chronologically and grouped under four headings that represent stages in Arnold's adult life and career: "The Young Poet, 1844-51 " "The Married Poet and Inspector of Schools, 1851-57," "The Professor of Poetry and Literary Critic, 1857-67," and "The Critic of Society and Religion 1867-88." In these letters, Arnold, who wrote no autobiography, tells the story of his life and expresses his intimate views on a variety of subjects. In order to include the largest possible selection of interesting letters from both previously published and unpublished sources, some of the letters are given in part while others are given in their complete form. Along with the most important letters from the 1895 edition by G. W. E. Russell - principally made up of letters to family members - and the 1932 edition of letters to Author Hugh Clough by Howard F. Lowry, this new collection incorporates many significant letters from other sources, including 49 previously unpublished letters. Most of the Russell and Lowry letters have been newly edited, using the manuscript collections at Yale University and Balliol College, Oxford.
Keywords: Arnold, Matthew <1822-1888> -- Correspondence; Arnold, Matthew -- 1822-1888; Geschichte 1800-1900; Critics -- Great Britain -- Correspondence; Poets, English -- 19th century -- Correspondence; Großbritannien; Briefsammlung